Menstrual cycle-based undulating periodized program effects on body composition and strength in trained women: a pilot studyLes effets d’un programme de périodisation ondulante, basé sur le cycle menstruel, sur la composition du corps et la force des femmes pratiquantes de musculation: une étude pilote - Vargas-Molina, Salvador; Petro, Jorge Luis; Romance-García, Ángel Ramón; Bonilla, Diego A.; Schoenfeld, Brad Jon; Kreider, Richard B.; Benítez-Porres, Javier (ELSEVIER, 2022)
Objective To evaluate changes in body composition and strength after menstrual cycle-based or traditional undulating resistance training (RT) programs in women. Equipment and methods Ten resistance-trained and eumenorrheic women (26.6 ± 3.0 years; 164.7 ± 6.5 cm; 62.3 ± 6.8 kg) were randomly assigned to a menstrual cycle-based periodized upper/lower training (n = 5, MC) or an undulating training group (n = 5, UT) for 8 weeks. The number of repetitions and load were adjusted to each phase of the menstrual cycle. Fat free mass (FFM) and fat mass (FM) were evaluated by dual x-ray absorptiometry (DXA); maximal strength was assessed by the 1 repetition maximum (1-RM) test in the back squat (SQ) and bench press (BP); and muscle power was assessed by the countermovement jump (CMJ) test using a jump contact mat. Results A significant increase in FFM was observed for UT (1.4 ± 0.9 kg, P = 0.043, ES = 0.58) with no difference in MC (1.7 ± 1.8 kg, P = 0.080, ES = 0.25). No changes in FM were observed for either condition (MC: 0.9 ± 1.2 kg, p = 0.225, ES = 0.21 and UT: 0.5 ± 1.0 kg, P = 0.345, ES = 0.13). Strength increases were observed for both MC an UT in the BP (8.9 ± 3.4 kg, p = 0.042, ES = 0.87 and 5.0 ± 1.8 kg, p = 0.039, ES = 0.67, respectively) and SQ (15.3 ± 9.2 kg, P = 0.043, ES = 0.93 and 16.4 ± 7.6 kg, P = 0.042, ES = 1.38, respectively). CMJ showed differences in MC (4.0 ± 2.5 cm, P = 0.043, ES = 1.12). We observed a between-group difference in BP (P = 0.041) favoring MC; no other interactions were found. Conclusions Eight weeks of a menstrual cycle-based periodized training combined with a hyperenergetic diet versus a non-matched undulating RT program have a differential impact on body composition and muscular adaptations in trained women.
Les effets d’un programme de périodisation ondulante, basé sur le cycle menstruel, sur la composition du corps et la force des femmes pratiquantes de musculation: une étude pilote
Keywords: Condición física; Resistance training; Bodybuilding; Sports nutrition; Sex hormones; Body fat